Автоматизована генерація програм для одного класу параметричних алгоритмів нейроеволюції - Дорошенко, А.Ю.; Ашур, І.З. (Проблеми програмування, 2022)
Застосовано апарат алгебри гіперсхем для автоматизованої генерації алгоритмів нейроеволюції на прикладі задачі оцінювання для двійкового мультиплексора, яка входить до складу системи SharpNEAT. Згадана система є фреймворком з відкритим програмним кодом мовою C#, що реалізує генетичний алгоритм нейроеволюції для платформи .NET. У статті показано, як за допомогою апарату алгебр алгоритмів та гіперсхем можна автоматизувати генерацію програм оцінювання для задач нейроеволюції. Гіперсхема є високорівневою параметризованою специфікацією алгоритму для розв’язання певного класу задач. Установка значень параметрів і подальша інтерпретація гіперсхеми дозволяє отримати алгоритми, адаптовані до конкретних умов застосування. Автоматизоване конструювання гіперсхем та генерація алгоритмів на їх основі виконується в розробленому інтегрованому інструментарії проєктування й синтезу програм. Проведено експеримент із виконання згенерованої програми для задачі оцінювання двійкового мультиплексора на розподіленій хмарній платформі The facilities of algebra of hyperschemes are applied for automated generation of neuroevolution algorithms on an example of a binary multiplexer evaluation problem, which is a part of the SharpNEAT system. SharpNEAT is an open-source framework developed in C# programming language, which implements a genetic neuroevolution algorithm for the .NET platform. Neuroevolution is a form of artificial intelligence, which uses evolution algorithms for creating neural networks, parameters, topology, and rules. Evolution algorithms apply mutation, recombination, and selection mechanisms for finding neural networks with behavior that satisfies to conditions of some formally defined problem. In this paper, we demonstrate the use of algebra of algorithms and hyperschemes for the automated generation of evaluation programs for neuroevolution problems. Hyperscheme is a high-level parameterized specification of an algorithm for solving some class of problems. Setting the values of the hyperscheme parameters and further interpretation of a hyperscheme allows obtaining algorithms adapted to specific conditions of their use. Automated construction of hyperschemes and generation of algorithms based on them is implemented in the developed integrated toolkit for design and synthesis of programs. The design of algorithms is based on Glushkov systems of algorithmic algebra. The schemes are built using a dialogue constructor of syntactically correct programs, which consists in descending design of algorithms by detailing the constructions of algorithmic language. The design is represented as an algorithm tree. Based on algorithm schemes, programs in a target programming language are generated. The results of the experiment consisting in executing the generated binary multiplexer evaluating program on a cloud platform are given.